2021
DOI: 10.1128/mra.00177-21
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Three SARS-CoV-2 P.1 Strains Identified from Patients Returning from Brazil to Italy

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the current coronavirus disease 2019 (COVID-19) pandemic. We report the complete sequences of three SARS-CoV-2 P.1 strains obtained from nasopharyngeal swab specimens from three patients returning from Brazil to Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…Thus, the surge of P.1 in this area strongly implies the possibility of reinfection [ 9 ]. An earlier study reported the presence of P.1 in three returning travelers from Brazil to Abruzzo sampled on 18 January 2021 [ 23 ], although we show here that this small cluster did not lead to (detectable) subsequent transmission events. A second study reported the presence of P.1 in a returning traveler from Brazil [ 28 ].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Thus, the surge of P.1 in this area strongly implies the possibility of reinfection [ 9 ]. An earlier study reported the presence of P.1 in three returning travelers from Brazil to Abruzzo sampled on 18 January 2021 [ 23 ], although we show here that this small cluster did not lead to (detectable) subsequent transmission events. A second study reported the presence of P.1 in a returning traveler from Brazil [ 28 ].…”
Section: Discussioncontrasting
confidence: 71%
“…The B.1.1.7 lineage appeared in all three areas within a five-day period, first in Central Italy (14 December) and five days later in both the North and South (19 December for both lineages) ( Figure 1 b). The first P.1 sequences were identified on 7 January 2021 in Central Italy in travelers returning from Brazil [ 23 ]. This lineage was subsequently found on 21 January and 12 February in North and South Italy, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, P.1 is still disseminating in all Brazilian regions as well as in other countries. 5,7,30,39,40 P.1 and P2 lineages have become predominant because of the high dissemination in the last months as clearly demonstrated in both skyline plots in this study. Also, the rates of nucleotide and amino acid substitutions were statistically higher in the P.1 lineage than P.2, suggesting a potential for greater transmissibility for the P.1 lineage.…”
Section: Discussionsupporting
confidence: 62%
“…Two main SARS-CoV-2 VOIs, P.1 and P.2, were discovered through active genomic surveillance performed in all regions of the country, both characterized by specific sets of significant amino acid substitutions: L18F, T20N, P26S, D138Y, R190S, K417T, E484K, N501Y, H655Y, and T1027I. 7,18,20,24,[39][40][41] In addition, both VOIs rapidly spread in the last 6 months. 7,8,19,20,24,[41][42][43] P.2 was first detected in July 2020 and represented 20% of all sequenced SARS-CoV-2 from this month until February 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal swab specimens were collected in the Abruzzo region between March and May 2021, and they were sent to the Istituto Zooprofilattico Sperimentale dell’Abruzzo e Molise (IZSAM) for SARS-CoV-2 RNA detection prior to genome sequencing ( 11 ). The SARS-CoV-2 diagnosis procedure was performed as previously described ( 12 ). An aliquot of 200 μl inactivated nasopharyngeal swab transport medium was employed for RNA extraction.…”
Section: Announcementmentioning
confidence: 99%